Bisphosphonates and risk of upper gastrointestinal cancer--a case control study using the General Practice Research Database (GPRD). - Ellen Wright (Public Library of Science (PLoS), 2012)
Background Concerns have been raised as to the safety of bisphosphonates; in particular a possible link between bisphosphonate use and upper gastrointestinal (GI) cancer. Two published studies using different study populations but drawn from earlier versions of the same national UK database, reached differing conclusions: one finding no evidence for an increase in the risk of gastric or oesophageal cancer in bisphosphonate users and one finding a small but significantly increased risk of oesophageal cancer linked to duration of bisphosphonate use. Methodology/ principal findings Design-A case control study comparing bisphosphonate prescribing in cases of upper GI cancer from 1995 to 2007 using UK primary care electronic health records (GPRD). Main Outcome Measure-Relative Risk (approximated to Odds Ratio for rare events) for oesophageal and gastric cancer development in bisphosphonate users compared to non-users. The odds of being a case of oesophageal cancer, adjusted for smoking status, were significantly increased in women who had had one or more bisphosphonate prescriptions, odds ratio 1.54 (95% CI 1.27-1.88) compared to non-users. There was no significant effect on gastric cancer in women, odds ratio adjusted for smoking status, 1.06 (95% CI 0.83-1.37) and also no apparent risk in men for either oesophageal or gastric cancer, odds ratio adjusted for smoking status 0.78 (95%CI 0.56-1.09) and 0.87 (95% CI 0.55-1.36) respectively. Conclusions/ significance Our results support a small but significant increased risk of oesophageal cancer in women prescribed bisphosphonates and is based on the largest number of exposed cases to date in the UK.